ANTAGONISME DAN POTENSI ISOLAT CENDAWAN ENDOFIT ASAL RIZOSFER TANAMAN BAWANG MERAH TERHADAP PATOGEN Alternaria porri - R Ratnawati; Kasman Jaya; I Idris; Sri Sudewi; Mar’atus Fitra (JURNAL GALUNG TROPIKA, 2022)
Using biological agents can suppress Pesticides in controlling purple spot disease caused by Alternaria porri in shallots. Antagonistic microorganisms as biological agents of can be obtained from shallot rhizosphere. This study aimed to determine the endophytic fungi from the rhizosphere. It were antagonistic to the pathogen Alternaria porri (Ell.Cif.) on shallots. This research was started by isolating the fungus by growing it on Potato Dextrose (PDA) media, and continued with purification, then identified microscopically. The identification results revealed the type of fungus in the shallot rhizosphere, namely Trichoderma sp. mf 1, Trichoderma sp mf 2, Fusarium sp mf 1, Fusarium mf 2, and Penicillium sp. each successively has the ability of inhibition against A. porri are 78.75%, 77.35%, 85.71%, 68.22%, and 67.60%. The isolates could suppress the growth of A.porri isolates and cause antagonistic mechanisms such as competition, antibiosis, and parasitism.